Augmentation of miR‐202 in varicose veins modulates phenotypic transition of vascular smooth muscle cells by targeting proliferator–activated receptor‐γ coactivator‐1α. Issue 6 (16th December 2018) - Huang, Xianchen; Liu, Zhao; Shen, Liming; Jin, Yiqi; Xu, Guoxiong; Zhang, Zhixuan; Fang, Changwen; Guan, Wenxian; Liu, Changjian
Abstract: In varicose veins, vascular smooth muscle cells (VSMCs) often show abnormal proliferative and migratory rates and phenotypic transition. This study aimed to investigate whether microRNA (miR)‐202 and its potential target, peroxisome proliferator–activated receptor‐γ coactivator‐1α (PGC‐1α), were involved in VSMC phenotypic transition. miR‐202 expression was analyzed in varicose veins and in VSMCs conditioned with platelet‐derived growth factor. The effect of miR‐202 on cell proliferation and migration was assessed. Furthermore, contractile marker SM‐22α, synthetic markers vimentin and collagen I, and PGC‐1α were analyzed by Western blot analysis. The modulation of PGC‐1α expression by miR‐202 was also evaluated. In varicose veins and proliferative VSMCs, miR‐202 expression was upregulated, with decreased SM‐22α expression and increased vimentin and collagen I expression. Transfection with a miR‐202 mimic induced VSMC proliferation and migration, whereas a miR‐202 inhibitor reduced cell proliferation and migration. miR‐202 mimic constrained luciferase activity in HEK293 cells that were cotransfected with the PGC‐1α 3′‐untranslated region (3′‐UTR) but not those with mutated 3′‐UTR. miR‐202 suppressed PGC‐1α protein expression, with no influence on its messenger RNA expression. PGC‐1α mediated VSMC phenotypic transition and was correlated with reactive oxygen species production. In conclusion, miR‐202 affects VSMC phenotypic transition by targeting PGC‐1α expression, providing a novel target for varicose vein therapy. Abstract : miR‐202 affects vascular smooth muscle cell (VSMC) phenotypic transition by targeting proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α) expression, providing a novel target for varicose vein therapy.